2019
DOI: 10.18280/acsm.430203
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on Flexural-tensile Performance of Polyester Fiber Asphalt Concrete

Abstract: Taking the AC-13F mixture as the matrix, this paper carries out beam bending tests on fiber asphalt concrete, using the optimal asphalt content (OAC) determined by Marshall test. The test parameters include temperature, fiber volume ratio and fiber aspect ratio. Based on the test results, the author systematically explored how the three parameters affect the flexural performance of asphalt concrete. In addition, the fiber content feature parameter (FCFP) was introduced to describe the combined effect of fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Fibrous materials, such as polyester fiber and mineral fiber, are generally added to enhance the working properties of asphalt. Wu et al explained that when polyester fiber is added to asphalt mixture, it is found that the flexural tensile strength of the asphalt mixture increases by 86.6% under the condition of optimal fiber content (0.4% by mass of asphalt mixture) (Chen F et al, 2019;Wu, J. et al, 2020). Mohammed et al added an appropriate amount of mineral fibers to the asphalt mixture to enhance its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous materials, such as polyester fiber and mineral fiber, are generally added to enhance the working properties of asphalt. Wu et al explained that when polyester fiber is added to asphalt mixture, it is found that the flexural tensile strength of the asphalt mixture increases by 86.6% under the condition of optimal fiber content (0.4% by mass of asphalt mixture) (Chen F et al, 2019;Wu, J. et al, 2020). Mohammed et al added an appropriate amount of mineral fibers to the asphalt mixture to enhance its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [ 16 ] pointed out that the addition of steel fiber improved the flexural tensile strength and anti-deformation ability of asphalt mixtures. Chen et al [ 17 ] proposed that polyester fibers could enhance the bending and tensile properties of mixtures. Wu et al [ 18 ] focused on the experimental research on the performance of basalt fiber-modified asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%